Parent Corporation Liability For Losses of State-Owned Enterprise Subsidiaries: A Substantive Control and Public Accountability Approach - Dicki Irvandi; Triono Eddy; Adi Mansar; Alief Risyawan (Jurnal Wawasan Yuridika, 2025)
The relationship between state-owned enterprises (SOEs) and their subsidiaries gives rise to an accountability dilemma when losses occur at the operational level of subsidiaries, as corporate law formally treats parent companies and subsidiaries as separate legal entities, while governance practices within SOE holding structures demonstrate substantive parental control through policy directives, business strategies, and the allocation of public capital. This misalignment between formal legal construction and the reality of substantive control creates an accountability gap in the management of state assets. This study aims to reconstruct the legal basis of parent SOE liability by positioning the intensity of substantive control as the principal variable of accountability. The research employs a normative legal method with doctrinal and comparative approaches, drawing on statutory analysis and conceptual examination of corporate law. The findings indicate that liability limitations based solely on the principle of separate legal personality are no longer adequate when subsidiaries carry out strategic projects shaped by state policy and public financing, as the parent SOE substantively contributes to the formation of risk and loss consequences. By adapting the doctrines of piercing the corporate veil and enterprise liability to the context of public entities, this study proposes a hybrid accountability model that links legal responsibility to actual patterns of control, thereby strengthening public accountability and preventing accountability gaps within state-owned corporate group structures.